The theory of economic growth - Lewis, W.Arthur (Homewood, Illinois : Richard D. Irwin, Inc, 1955)
The purpose o f the book is to try to provide an appropriate framework for studying economic development.
Includes index.
rpm 24/01/2019
Loans
Keywords: Economics; Economic theory